2022
DOI: 10.29244/jfs.v7i2.41937
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Work-Family Conflict, Communication Pattern, Social Support, and Stress Levels toward Family Quality of Life During The Covid-19 Pandemic

Abstract: Staying at home during the pandemic COVID-19 should be an opportunity to improve the family's quality of life (QoL). Positively, gathering with family at home provides an opportunity to get to know family members in-depth, but also prone to causing various frictions due to the boundary between office work, housework, and family becoming invisible. This study aims to analyze the effect of work-family conflict, communication patterns, social support, and stress levels on the family quality of life before and dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Research shows that limited communication between adolescents and parents is one of the causes of bullying. In line, Ramadhanti et al (2022) found that families with high communication patterns during the pandemic showed that family members were more open in expressing opinions. Interpersonal communication in the family is a family resource that can help adolescents develop identity and openly convey their problems (Ramadhana et al, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…Research shows that limited communication between adolescents and parents is one of the causes of bullying. In line, Ramadhanti et al (2022) found that families with high communication patterns during the pandemic showed that family members were more open in expressing opinions. Interpersonal communication in the family is a family resource that can help adolescents develop identity and openly convey their problems (Ramadhana et al, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…As in the study by Ramadhanti et al (2022), which states that for families with mothers working in the formal sector, the challenges of obtaining employment in Indonesia and the workforce will become increasingly difficult. All the responsibilities placed on women trigger an increase in stress levels.…”
Section: Discussionmentioning
confidence: 99%